Kahf's Public Relations Strategy to Build Halal and Masculine Skincare Image: Strategi Public Relations Kahf Membangun Citra Skincare Halal dan Maskulin - Siagian, Ariati Putri; Nurhanifah, Nurhanifah (Indonesian Journal of Innovation Studies, 2025)
General Background: The halal skincare industry in Indonesia is experiencing significant growth in line with increasing consumer awareness of halal products. Specific Background: Kahf, a local brand under PT Paragon Technology and Innovation, positions itself as a halal and masculine skincare brand targeting Indonesian Muslim men. Knowledge Gap: Despite its strong brand identity, Kahf faces challenges in sustaining a positive brand image amidst intense competition from local and global skincare brands. Aims: This study aims to explore the Public Relations (PR) strategies employed by Kahf and assess their effectiveness in shaping consumer perceptions. Results: Utilizing a descriptive qualitative approach, data were collected through documentation studies, non-participant observations of Kahf’s Instagram and TikTok accounts, and interviews with product users. The findings indicate that Kahf’s PR strategies—centered on modern Islamic values—are effective in reinforcing its image as a halal, modern, and relevant brand for Indonesian Muslim men. Novelty: This study highlights the strategic integration of religious identity within brand communication in the halal skincare sector, an area underexplored in current literature. Implications: The results offer valuable insights for marketing practitioners, emphasizing the importance of culturally and religiously resonant communication in building brand loyalty and trust in highly competitive markets. Highlights: Highlights how PR shapes halal brand identity in a competitive market. Emphasizes the role of modern Islamic values in brand communication. Offers strategic insights for targeting Muslim male consumers effectively. Keywords: Public Relations, Brand Image, Kahf, Halal Skincare, Muslim Consumers